МАҲАЛЛИЙ ВА ИНТРОДУКЦИЯ ҚИЛИНГАН ЎРИК НАВЛАРИНИНГ ҚИММАТЛИ ХЎЖАЛИК БЕЛГИЛАРИ - С. Я. Исламов, А.Э. Қаршиев, Б.Э.Юсупова (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
the article presents scientific observations conducted in order to study domestic and foreign varieties of apricot bushes and select promising varieties, as well as reduce various parameters and correct formation of hornbeam on trees during annual pruning of varieties, improve fruit quality, adaptability to external conditions and other positive characteristics.